Chlorhexidine Cleansing of the Umbilical Cord for Prevention of Umbilical Infection: A Hospital based Study in Bangladesh (Bangladesh Journal of Child Health, 2018)
Background: The umbilical cord is an important site for bacterial colonization. A possible consequence of bacterial colonization is cord stump infection, a factor that can greatly increase morbidity and mortality for infants in developing countries. Chlorhexidine cleansing of the cord can reduce neonatal mortality among newborns infants in low-resource settings with high risk of infection. This objective of this study was to determine the effect of cord cleansing with chlorhexidine in reduction of umbilical infection among newborns in hospital settings.Methodology: Between April 2013 to July 2014, 510 newborns were randomly assigned within a tertiary level hospital in Bangladesh to receive 1 of 3 cord care regimens: single cord cleansing with 4% chlorhexidine(Group-1), multiple cord cleansing with 4% chlorhexidine (Group-2) and clean and dry cord care (Group-3 : control).Results: The risk of umbilical cord infection (omphalitis) was significantly reduced in both the single (Relative risk [RR] 0.15 [95% CI] 0.008-0.93) and multiple chlorhexidine cleansing group (RR 0.37 [95% CI] 0.04- 0.99) compared to the dry cord care group. The risk of omphalitis was not significantly different between multiple and single chlorhexidine cleansing group (RR 3.14 [0.13-76.54]).Conclusion: 4% chlorhexidine significantly reduce the risk of umbilical infection in both single and multiple cord cleansing groups as compared to clean and dry cord care group.Bangladesh J Child Health 2018; VOL 42 (1) :4-8